Peran Good Corporate Governance, Corporate Social Responsibility serta Capital Intensity dalam Tax Avoidance - Fransisca, Angel; Rahayuningsih, Deasy Ariyanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This study aimed is to test and provide empirical evidence of the role of good corporate governance, corporate social responsibility, and capital intensity on tax avoidance. This study uses tax avoidance as the dependent variable measured by the CETR. The population in this study were manufacturing companies listed on the IDX in 2019-2021. The number of samples that were successfully obtained using the purposive sampling method were 53 companies with a total of 159 data. This study to determine the effect of institutional ownership, independent commissioner, audit committee, audit quality, corporate social responsibility, and capital intensity on tax avoidance. The results showed that audit committee had a positive effect on tax avoidance. Meanwhile institutional ownership has not effect on tax avoidance because institutional owners do not carry out good supervision and have the potential for tax avoidance to occur, independent commissioners has no effect on tax avoidance because independent commissioners have not been able to carry out their obligations to avoid tax avoidance, audit quality has no effect on tax avoidance because KAP does not have the authority to tax companies, CSR has no effect on tax avoidance because the amount of CSR disclosure does not affect corporate tax payments. Capital intensity has no effect on tax avoidance because fixed assets that have passed the age limit cannot be used as a deduction from pre-tax profit.